Reposisi Filosofi Pendidikan Dalam Proses Pembelajaran - Rita Sulastini (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Learning process trully combine between what’s learning aims and what’s the essential learning, because too much interaction on process happened. Educational philosophy became an essential process, to be normative direct in many condition. Educational philosophy trully play its role as a catalis, which is not just connected between cognitive knowledge, but enrichment also. Each learning process needs ’space’ to learn deeply dedicated that can build an ecological environment which give more access to learn. At the end, on many situation, educational philosophy substantial have to bring and mapped what the truly learning aims. Keyword: Filosofis pembelajaran, Ruang pembelajaran, Proses interaksi